Mitochondrial Defects Drive Degenerative Retinal Diseases - Ferrington, Deborah A. (Trends Mol Med, 2019)
Mitochondrial dysfunction is involved in the pathology of two major blinding retinal diseases, Diabetic Retinopathy (DR) and Age-related Macular Degeneration (AMD). These diseases accumulate mitochondrial defects in distinct retinal subcellular structures, the vascular/neural network in DR and the retinal pigment epithelium in AMD. These mitochondrial defects cause a metabolic crisis that drives disease. With no treatments to stop these diseases, coupled with an increasing population suffering from AMD and DR, there is an urgent need to develop new therapeutics targeting the mitochondria to prevent or reverse disease-specific pathology.